Dietary Moringa oleifera improves growth performance, oxidative status, and immune related gene expression in broilers under normal and high temperature conditions. (May 2019) - El-Deep, Mahmoud H.; Dawood, Mahmoud A.O.; Assar, Mohamed H.; Ijiri, Daichi; Ohtsuka, Akira
Abstract: The aim of this study is to evaluate the effects of Moringa oleifera (MO) on the performance, antioxidative status, and immune related gene expression in broilers raised under normal or heat stress conditions. Broiler chickens were distributed into 4 groups and fed diets with dietary MO at 0% or 5% (MO0 or MO5) and raised under ambient temperature 22 ± 1 °C (N) or 35±1 °C (HS). HS conditions negatively affected the weight gain and FCR, while feeding MO exhibited beneficial effects especially under HS conditions. Triglycerides, total cholesterol and low-density lipoprotein cholesterol (LDL) levels were significantly ( P < 0.05) higher in chickens raised in HS conditions and fed the basal diet than those in normal condition and fed with or without MO, while MO decreased triglycerides and total cholesterol levels in normal and HS conditions. Blood high-density lipoprotein cholesterol (HDL) was significantly decreased in broilers raised in HS conditions and fed diets without MO, while MO increased HDL level. Blood glutathione peroxidase (GSH-Px) was significantly ( P < 0.05) decreased in broilers raised in HS conditions and fed the basal diet without MO. mRNA expression of GSH-Px was significantly ( P < 0.05) downregulated in broilers raised in HS conditions and fed diets without MO. Broilers under normal or HS conditions and fed the basal diet exhibited significantly ( P < 0.05) downregulated mRNA expressions of superoxide dismutase (SOD) and catalase (CAT) compared to chickens under normal conditions and fed MO. Liver and muscle thiobarbituric acid reactive substance (TBARs) were significantly ( P < 0.05) increased in broilers under HS conditions and fed diet without MO. The expressions of interleukins (IL2 and IL6) were significantly ( P < 0.05) downregulated in broilers under normal or HS conditions and fed diets without MO. To sum up, HS conditions depressed the performance, antioxidative status, and immune related gene expression in broilers, while MO obviously alleviated these negative effects in broilers. Highlights: Heat stress (HS) in broiler chickens negatively affects performance. The use of Moringa oleifera (MO) in the diet of broiler promoted the growth and feed efficiency. The use of MO in diet stimulated the antioxidant system in normal and HS conditions. MO in diet reduced the lipid peroxidation in normal and HS conditions. MO in diet of broilers was able to upregulate the immune related gene expression in normal and HS conditions.